A Rationale for Further Herd Expansion on Florida Dairies - Russell Giesy; Albert de Vries (EDIS)
This document is AN133, one of a series of the Animal Sciences Department, Florida Cooperative Extension service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2002.